Pengaruh Diabetes Self Management Education and Support (DSME/S) Terhadap Stres Pada Pasien Diabetes Melitus (DM) Tipe 2 Di Wilayah Kerja Puskesmas Patrang Kabupaten Jember (The Effect of Diabetes Self-Management Education and Support [DSME/S] on Stress i - Siti Marina Wiastuti; Rondhianto Rondhianto; Nur Widayati (Pustaka Kesehatan, 2017)
Diabetes Mellitus (DM) is a chronic disease that needs a sustainable self-care. Low-level knowledgeof self-care can worsen health condition and cause stress. DSME/S is an ongoing process tofacilitate knowledge, skill, and abilities required to perform self-care. This research aimed to analyzethe effect of DSME/S on stress in patients with type 2 DM. The design was quasi-experimental withrandomized control group pretest-posttest design. The sample size was 30 respondents which wererandomly divided into 15 respondents as the intervention group and 15 respondents as the controlgroup. DSME/S was conducted once per week for 6 weeks with 150 minutes for each encounter.The measurement of stress was measured by using Diabetes Distress Scale (DDS). The data wereanalyzed by using dependent t test and independent t test with significance level of 0.05. The resultof dependent t test revealed a significant difference of stress between pretest and posttest both inthe intervention group (p = 0.000) and in the control group (p = 0.000). Furthermore, independent ttest showed a significant difference between intervention group and control group (p = 0.001) sothat there was a significant effect of DSME/S on stress in patients with type 2 Diabetes Mellitus.Keywords : stress, DSME/S, diabetes mellitus